Guidelines for developing problem-solving processes in the learning of teacher students, Sakon Nakhon Rajabhat University - Dutthuyawat, Amporn (MCU Haripunchai Review, 2024)
The purpose of this research is to: 1) study the problem-solving elements in the learning of students of the teaching profession; 2) Study the actual and supposed conditions regarding the problem-solving process in the learning of students of the teaching profession. 3) Assess the need to develop a problem-solving process in the learning of students of the teaching profession, and 4) Seek ways to develop a problem-solving process in the learning of students of the teaching profession. The sample group is students of the teaching profession. Sakon Nakhon Rajabhat University Academic Year 2023 Determine the sample size using Krejci and Morgan’s table. A total of 342 participants were obtained by multi-stage randomization. The instrument is a 5-level estimation scale questionnaire with a consistency index between .80 - 1.00, the actual condition has a classification power between .52 - .79 with a confidence of .96, the supposed condition has a classification power between .50 - .90 and a confidence of .97. The statistics used include percentage, mean, standard deviation, and the Modified Priority Needs Index. The results of the research showed that 1) the problem-solving process component of learning among students of the teaching profession; There are 7 components, all of which are appropriate at the highest level. 2) The actual condition regarding the problem-solving process in the learning of students of the teaching profession, both overall and individually, is moderate. As for the condition that should be both overall and individual at the highest level. 3) The results of the assessment of the need to develop problem-solving processes in the learning of students of the teaching profession; Overall, the Needs Priority Index was .216. 4) The elements used to find development approaches include problem identification, problem analysis. Problem solving and reflection